Collective Perception and Exchange Rates. Issue 1 (2nd January 2019) - Reed, Markum; Ankouri, Kaotar
ABSTRACT: The authors' research suggests that people search online for information on currency exchange rates and that this information-seeking process can be translated into data on people's interest for a given currency. The authors utilize Google Trends data to capture the level of interest in 3 currency pairs: the euro, the pound sterling, and the Canadian dollar against the U.S. dollar and conduct a multivariate data analysis in the context of vector-autoregressive models. The findings suggest that there is a small but significant impact on collective perception on exchange rates. The authors show that Google Trends data could be an important source of information for investors looking into exchange rate trends.